2007
DOI: 10.1111/j.1365-2850.2007.01111.x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary usability evaluation of Web‐based portal application for patients with schizophrenia

Abstract: This study evaluated the usability of a Web-based portal application developed for the use of nursing staff with patients suffering from schizophrenia and related psychosis. The study was designed solely to gain direct inputs from the nursing staff (N = 76, n = 38) in acute inpatient wards in two Finnish psychiatric hospitals. The data were collected by questionnaire covering the functionality, content and benefits of the portal. The evaluation showed that the portal is user-friendly enabling a user to move in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…These include portals for patients with diabetes,2531 COPD,32 asthma,33 breast cancer,34 attention-deficit/hyperactivity disorder,35 and schizophrenia 36. Web portals have also been developed to meet the needs of particular patient populations, including pediatric patients and their guardians,35,37,38 maternity patients,39 patients receiving in vitro fertilization,40 and older adults 41.…”
Section: Resultsmentioning
confidence: 99%
“…These include portals for patients with diabetes,2531 COPD,32 asthma,33 breast cancer,34 attention-deficit/hyperactivity disorder,35 and schizophrenia 36. Web portals have also been developed to meet the needs of particular patient populations, including pediatric patients and their guardians,35,37,38 maternity patients,39 patients receiving in vitro fertilization,40 and older adults 41.…”
Section: Resultsmentioning
confidence: 99%
“…Koivunen et al (26) reported on an interactive, multiservice, on-line portal application called Mieli.net designed to help support patients with schizophrenia spectrum disorders as well as hospital staff nurses caring for these patients. The content and the structure of the portal were designed based on a needs analysis of both patients and staff.…”
Section: Resultsmentioning
confidence: 99%
“…The data originally came from a large-scale national research project (Mieli.Net, Academy of Finland 207384) where a computer-based self-management system for patients with SSDs was developed and tested3538 from a variety of perspectives.…”
Section: Methodsmentioning
confidence: 99%